2023
DOI: 10.1128/jvi.01941-22
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of VP1 Mediated by CDK1-Cyclin B1 Facilitates Infectious Bursal Disease Virus Replication

Abstract: Infectious bursal disease virus still poses a great economic threat to the global poultry farming industry. Detailed information on the steps of viral genome replication is essential for the development of antiviral therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Besides the down regulation of CDK1, our findings indicate a significant down-regulation of genes associated with the protein synthesis system as evidenced by extensive down-regulated genes enriched in the ribosome-related pathway, RNA transport, spliceosome, ribosome biosynthesis in eukaryotes. Recently, Wu and Hur (60) confirmed that the CDK1-cyclin B1 complex phosphorylates VP1, thereby facilitating IBDV replication. Collectively, these results suggest that NN1172 may arrest cell cycle at G2/M stage, which may enhance virus replication, thymus damage and disease progresses.…”
Section: Discussionmentioning
confidence: 98%
“…Besides the down regulation of CDK1, our findings indicate a significant down-regulation of genes associated with the protein synthesis system as evidenced by extensive down-regulated genes enriched in the ribosome-related pathway, RNA transport, spliceosome, ribosome biosynthesis in eukaryotes. Recently, Wu and Hur (60) confirmed that the CDK1-cyclin B1 complex phosphorylates VP1, thereby facilitating IBDV replication. Collectively, these results suggest that NN1172 may arrest cell cycle at G2/M stage, which may enhance virus replication, thymus damage and disease progresses.…”
Section: Discussionmentioning
confidence: 98%
“…Infectious bursal disease virus (IBDV), a segmented dsRNA virus belonging to the Birnaviridae family, infects B lymphocytes in the bursa of Fabricius and causes a highly contagious, acute, and immunosuppressive infectious bursal disease in young chickens. The RNA-dependent RNA polymerase protein VP1 is involved in viral genome replication, transcription, and packaging, and its catalytic activity can be regulated by PTMs, such as sumoylation and phosphorylation 144 , 145 . Arginine methylation by PRMT also affects VP1 activity and viral infection (Figure 7 A).…”
Section: Prmts Regulate Viral Infectionmentioning
confidence: 99%
“…For instance, in the case of SARS-CoV-2, nsp12 was shown to recruit CDK2 through its NiRAN domain (13). The polymerase of infectious bursal disease virus (IBDV) can interact with the CDK1-cyclinB1 complex (11). Polymerases of several flaviviruses including West Nile virus, Usutu virus, Zika virus and HCV were all shown to interact with AKT/PKB and to be phosphorylated by these kinases in vitro (19, 34).…”
Section: Recruitment Of Host Kinases By Protein-protein Interactionmentioning
confidence: 99%